Investigation of Health System Assumptions in Curriculum of Fourth Grade Elementary Textbooks Using Shannon Entropy Content analysis - mohammad azimi (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Health education is an inseparable part of a curriculum for all students. Health education should represent the essential knowledge, attitudes, and skills. So, the present research aimed at investigating health system assumptions in fourth-grade elementary textbooks. Method: This research is applied and descriptive-analytical has been done manually by Shannonchr('39')s entropy content analysis, which suggests a quantitative approach to data processing. The research has investigated the respondentschr('39') viewpoints about the content of fourth-grade elementary textbooks and 12 major components (Physical health, Nutritional health, Environmental health, Natural environment health, Family health, Safety incidents, Physical activity, Mental health, Prevention of high-risk behaviors, Control, and prevention of diseases, Disability, Public health, and school health) and 58 minor components of health education and promotion. Results: In this research, all fourth-grade elementary textbooks have been reviewed. According to Shannonchr('39')s entropy content analysis results, mental health has the highest frequency with 277 components, and disability has the least frequency with 12 components. Among the 1157 health components in fourth-grade elementary textbooks, there are 81 physical health components, 263 nutritional health components, 57 environmental health components, 33 natural environment health components, 227 family health components, 19 safety incident components, 73 physical activity components, 277 mental health components, 25 component of prevention of high-risk behaviors, 14 components of disease control and prevention, 12 disability components, and 58 components of public health and school health. Conclusion: According to the content analysis, there is no normal distribution between the components of health education and health promotion among the components studied in the content of the fourth-grade books, so that little attention has been paid to health education components in fourth-grade elementary textbooks.